Neuropathic pain prevalence following spinal cord injury: A systematic review and meta‐analysis. (24th June 2016) - Burke, D.; Fullen, B.M.; Stokes, D.; Lennon, O.
Abstract: Following spinal cord injury (SCI), chronic pain is a common secondary complication with neuropathic pain (NP) cited as one of the most distressing and debilitating conditions leading to poor quality of life, depression and sleep disturbances. Neuropathic pain presenting at or below the level of injury is largely refractory to current pharmacological and physical treatments. No consensus on the prevalence of NP post SCI currently exists, hence this systematic review was undertaken. The review comprised three phases: a methodological assessment of databases [PubMed, Embase, Web of Knowledge, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library and Physiotherapy Evidence Database (PEDro)] identifying potential papers and screening for inclusion criteria by two independent reviewers; data extraction; and finally rating of internal validity and strength of the evidence, using a published valid and reliable scale. Meta‐analysis estimated pooled point prevalence rates using a random effects model. In total, 17 studies involving 2529 patients were included in the review. Overall point prevalence rates for NP were established at 53% (38.58–67.47); 19% (13.26–26.39) for at‐level NP and 27% (19.89–34.61) for below‐level NP, with high heterogeneity noted ( I 2 = 84–93%). Prevalence rates for NP following SCI are high. Future studies should include established definitions, classification systems and assessment tools for NP at defined time points post SCI to follow the trajectory of this problem across the lifespan and include indices of sleep, mood and interference to allow for appropriate, optimal and timely NP management for each patient. What does this review add?: This is the first systematic review and meta‐analysis to record pooled point prevalence of neuropathic pain post spinal cord injury at 53%. Additional pooled analysis shows that neuropathic pain is more common below the level of lesion, in patients with tetraplegia, older patients and at 1 year post injury.